Hormonal Control of Parthenocarpic Ovary Growth by the Apical Shoot in Pea - Rodrigo, María J. (American Society of Plant Physiologists, 1998)
The role of the apical shoot as a source of inhibitors preventing fruit growth in the absence of a stimulus (e.g. pollination or application of gibberellic acid) has been investigated in pea (Pisum sativum L.). Plant decapitation stimulated parthenocarpic growth, even in derooted plants, and this effect was counteracted by the application of indole acetic acid (IAA) or abscisic acid (ABA) in agar blocks to the severed stump. The treatment of unpollinated ovaries with gibberellic acid blocked the effect of IAA or ABA applied to the stump. [(3)H]IAA and [(3)H]ABA applied to the stump were transported basipetally, and [(3)H]ABA but not [(3)H]IAA was also detected in unpollinated ovaries. The concentration of ABA in unpollinated ovaries increased significantly in the absence of a promotive stimulus. The application of IAA to the stump enhanced by 2- to 5-fold the concentration of ABA in the inhibited ovary, whereas the inhibition of IAA transport from the apical shoot by triiodobenzoic acid decreased the ovary content of ABA (to approximately one-half). Triiodobenzoic acid alone, however, was unable to stimulate ovary growth. Thus, in addition to removing IAA transport from the apical shoot, the accumulation of a promotive factor is also necessary to induce parthenocarpic growth in decapitated plants.